2015
DOI: 10.20491/isader.2015115761
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reasons for Organizational Silence of Nurses

Abstract: ÖzetSağlık personeli arasında büyük bir çoğunluğu oluşturan ve hasta bakımından birinci derecede sorumlu olan hemşirelerin örgüt içinde sessiz kalma nedenlerini belirlemek, bu nedenlerin hemşirelerin tanımlayıcı özelliklerine göre farklılaşıp farklılaşmadığını ortaya koymak ve sessizlik nedenlerine ilişkin boyutların kendi aralarındaki ilişkiyi belirlemek, bu araştırmanın amacını oluşturmaktadır. Araştırmanın örneklemi, bir üniversite hastanesinde görev yapan 237 hemşiredir. Araştırma sonucunda, hemşirelerin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 1 publication
4
9
2
2
Order By: Relevance
“…However, when compared to studies conducted in the nurse population, our finding is contrary to earlier studies wherein higher levels of silence were observed in nurses who have been in the profession for a longer time (Bayın, Yeşilaydın, & Esatoglu, 2015; Seren et al., 2018). Bayın et al (2015) and Seren et al. (2018) attributed such silence among nurses to familiarity with the organisation and the style of management among nurse managers.…”
Section: Discussioncontrasting
confidence: 99%
“…However, when compared to studies conducted in the nurse population, our finding is contrary to earlier studies wherein higher levels of silence were observed in nurses who have been in the profession for a longer time (Bayın, Yeşilaydın, & Esatoglu, 2015; Seren et al., 2018). Bayın et al (2015) and Seren et al. (2018) attributed such silence among nurses to familiarity with the organisation and the style of management among nurse managers.…”
Section: Discussioncontrasting
confidence: 99%
“…Another cause of this difference could be ascribed to the diminished fear that the employees, who have earned retirement in the public institutions, have of losing their job. Bayın et al (2015) reported that people remained silent less often about administrative and organisational issues as they got older; a finding that was consistent with this study's results.…”
Section: Discussionsupporting
confidence: 90%
“…Bayın et al . () reported that people remained silent less often about administrative and organisational issues as they got older; a finding that was consistent with this study's results.…”
Section: Discussionsupporting
confidence: 89%
“…“Administrative and organisational reasons” was ranked second by nurses in Çaylak and Altuntaş study (). Bayın, Yeşilaydın, and Esatoğlu study () reported “Administrative and organisational reasons” and “Fear of isolation” near the top among reasons of organisational silence. Findings of this study confirm previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Bayın et al. () stated that the reason why especially experienced nurses kept more silent was associated with the fact that they knew the organisational culture and management style well.…”
Section: Discussionmentioning
confidence: 99%